The Prose of the mountains : three tales of the Caucasus - Qazbegi, Alekʻsandre, 1848-1893 (CEU Press classics., 2015)
"Georgian Notes on the Caucasus translates and introduces three classic stories by the Georgian writer Aleksandre Qazbegi (1848-1893) to the Anglophone reading public. "Memoirs of a Shepherd" poignantly chronicles the author's decision to pass seven years of his life as a shepherd with Georgian mountaineers. "Eliso" offers one of the most searing accounts on record of the Chechens' forced migration from their homeland to Ottoman lands. "Khevis Beri Gocha" is a classic tale, set in the sixteenth-century, of a tragic misunderstanding between a severe father and his loving son. Although little known outside his native country, Qazbegi was one of the most prescient and gifted chroniclers of the Georgian encounter with colonial modernity. His stories offer an invaluable counterpoint to the predominantly Russian narratives that have hitherto shaped scholarly accounts of the nineteenth century Caucasus. In addition to presenting Qazbegi's influential and compelling accounts of mountaineer Georgian and Chechen lives under colonial rule for the first time in English, I introduce the reader to Qazbegi's achievement in historical and literary terms through a scholarly and critical apparatus that includes a preface, afterword, glossary, and annotations"--